Meroe, the city of the Ethiopians; being an account of a first season’s excavations on the site, 1909-1910 - Garstang, J.; Sayce, A.H.; Griffith, F.LL. (Clarendon Press, Oxford., 1911)
At the suggestion of Professor Sayce, and aided by the facilities granted by the Government of the Sudan, the Liverpool University Institute of Archaeology was enabled to commerce excavations on the site of Meroe during the winter season 1909 – 1910.
Keywords: Excavations; Ethiopia; Meroe